The common octopus fishery in South Portugal: a new shelter-pot - Borges, Teresa C. (2016)
The octopus is one of the most important marine resources in Portugal, especially in the South, the Algarve region. The fishing gears mostly used are the “alcatruz” and the “covo”. The “alcatruz” is a shelter-pot traditionally made of clay, with an amphora shape, but recently plastic cylindrical pots were introduced and became more popular. “Covos” are baited metal cage-traps covered by a plastic net. Although very popular among fishermen, the traditional “alcatruz” made of clay has been replaced by cylindrical plastic pots with great success, due to its resistance to brake. In an attempt to continue using the traditional amphora-shape, a new type of plastic pot was built in association with fishermen. To study the behaviour of the common octopus (Octopus vulgaris) towards the traditional amphora clay shelter-pot, the cylindrical plastic shelter-pot and the new amphora plastic shelter-pot, several experiments were performed in controlled tanks. Three main questions were attempted to answer concerning the preferences of the common octopus towards the pots: 1) What kind of material: plastic or clay (traditional); 2) What shape: cylindrical or amphora (traditional); 3) What colour: white, black or red brick (traditional). The results showed no particular preference towards the material of the fishing gear; a strong preference for the traditional amphora shape; and a strong preference for the black colour.